L1 INFLUENCE ON VIETNAMESE ACCENTED ENGLISH - Anh, Ngo Phuong (Kajian Linguistik dan Sastra, 2009)
âEach variety of English in the world has its own distinctive features which areassociated with various reasons. The research aims primarily at discovering whetherL1 strongly influences Vietnamese accented English or not. In order to meet thisaim, the research focuses on: (1) identifying phonological similarities and dissimilarities between Vietnamese and English vowels and consonants based on bothacoustic and articulatory features; (2) investigating acoustic features of Vietnamese English vowels; (3) answering the question of whether the pronunciation of thespeakers is influenced by the phonological differences and similarities. This research is of descriptive type and the method adopted is a mixture of qualitative andquantitative approach. Acoustic data are gleaned from 6 recordings made by sixVietnamese informants. The measurements of sounds are figured out by means ofWave-surfer program. The result of the study shows that Vietnamese accented English is strongly influenced by the dissimilarities between Vietnamese and English.Keywords: Vietnamese English, Segmental and Supra-segmental errors, vowels/consonants similarities and dissimilarities